Characteristics of Lawyers Who Are Subject to Complaints and Misconduct Findings. Issue 2 (17th April 2019) - Sklar, Tara; Taouk, Yamna; Studdert, David; Spittal, Matthew; Paterson, Ron; Bismark, Marie
Abstract : Regulators of the legal profession are charged with protecting the public by ensuring lawyers are fit to practice law. However, their approach tends to be reactive and case based, focusing on the resolution of individual complaints. Regulators generally do not seek to identify patterns and trends across their broader caseloads and the legal profession as a whole. Using administrative data routinely collected by the main regulator of the legal profession in Victoria, Australia, we characterized complaints lodged between 2005 and 2015 and the lawyers against whom they were made. We also analyzed risk factors for complaints and misconduct findings. We found that the odds of being subject to a complaint were higher among lawyers who were male, older, had trust account authority, and whose legal practices were smaller, in nonurban locations, and incorporated. A deeper understanding of these risk factors could support efforts to improve professional standards and reform regulatory practices.